Ultraviolet phototherapy for treatment of various dermatoses - Irwan Saputra Batubara; Larisa Paramitha Wibawa; Erdina Pusponegoro; Windy Keumala Budianti; Githa Rahmayunita; Shannaz Nadia Yusharyahya (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Ultraviolet (UV) radiation has been applied to treat many chronic skin diseases. Based on the wavelength, UV radiation consists of three types, namely ultraviolet C (UVC), ultraviolet B (UVB), and ultraviolet A (UVA). The types of UV that are widely used in dermatology are narrowband ultraviolet B (NB-UVB), broadband ultraviolet B (BB-UVB), UVA1, and psoralen combined with UVA (PUVA). The interaction between UV and the skin determines the effectiveness of phototherapy. The biological effects of UV are used in the management of inflammatory skin diseases, malignancies, and various rare dermatoses. Apart from these benefits, UV increases the risk of photoaging and skin cancer. Therefore, further researches are necessary to enhance the effectiveness and safety of phototherapy. This literature review discusses the role of phototherapy in various dermatoses other than psoriasis and vitiligo.